203 Opioid Reduction After SCS. (1st April 2022) - Hatcher, Stacy; Jacobs, David; Air, Ellen L.
Abstract : INTRODUCTION: Spinal cord stimulation (SCS) is frequently used as a primary method to treat intractable back and extremity pain with the secondary goal of replacing or reducing adjunct opioid use. Our study investigates pre and post-operative changes in morphine milligram equivalents (MME) for patients who have undergone SCS. METHODS: Data was extracted from the Henry Ford Department of Neurosurgery RedCap spinal cord stimulator database. Descriptive statistics of means, standard deviations, medians, interquartile ranges (IQR) and percentages were computed for the outcomes of interest. Signed rank tests were done to compare pre to post measurements of MME. The testing level was set at 0.05 and all analyses were done using SAS version 9.4. RESULTS: There were a total of 241 cases included in the RedCap SCS database out of which 196 were included in our analysis. A significant reduction was seen in the use of opioid pain medication from the pre-operative MME measurement as compared to the 3-month postoperative MME measurement (median = 9.5, IQR = (0, 27.5), p < 0.001). However, the differences in opioid use between pre and postoperative week 6 and 2-year measurements were not significant. CONCLUSION: SCS has traditionally been used in patients with intractable back and/or extremity pain and potentially helps to decrease opioid use as the primary method of pain relief in these patients. Careful consideration should be given when choosing candidates for SCS implantation as well a long-term follow up to track post-operative MME use.